Challenges for Clinical Development of Vaccines for Prevention of Hospital-Acquired Bacterial Infections - Bekeredjian-Ding, Isabelle (Frontiers in Immunology, 2020)
Increasing antibiotic resistance in bacteria causing endogenous infections has entailed a need for innovative approaches to therapy and prophylaxis of these infections and raised a new interest in vaccines for prevention of colonization and infection by typically antibiotic resistant pathogens. Nevertheless, there has been a long history of failures in late stage clinical development of this type of vaccines, which remains not fully understood. This article provides an overview on present and past vaccine developments targeting nosocomial bacterial pathogens; it further highlights the specific challenges associated with demonstrating clinical efficacy of these vaccines and the facts to be considered in future study design. Notably, these vaccines are mainly applied to subjects with preexistent immunity to the target pathogen, transient or chronic immunosuppression and ill-defined microbiome status. Unpredictable attack rates and changing epidemiology as well as highly variable genetic and immunological strain characteristics complicate the development. In views of the clinical need, re-thinking of the study designs and expectations seems warranted: first of all, vaccine development needs to be footed on a clear rationale for choosing the immunological mechanism of action and the optimal time point for vaccination, e.g. 1.) prevention (or reduction) of colonization versus prevention of infection and 2.) boosting of a preexistent immune response versus altering the quality of the immune response. Furthermore, there are different, probably redundant, immunological and microbiological defense mechanisms that provide protection from infection. Their interplay is not well understood but as a consequence their effect might superimpose vaccine-mediated resolution of infection and lead to failure to demonstrate efficacy. This implies that improved characterization of patient subpopulations within the trial population should be obtained by pro-and retrospective analyses of trial data on subject level.Statistical and systems biology approaches could help to define immune and microbiological biomarkers that discern populations that benefit from vaccination from those where vaccines might not be effective.